Notice from Chief Editor - Zhang, Zhi-Qiang (Zootaxa, 2005)
The first issue of Zootaxa was published on 28 May 2001. On 27 May 2005, Zootaxa 1000 was published. In four years, over 1100 authors from all over the world had published 1000 papers/monographs in more than 23000 pages. Papers range from 4 to 1295 pages. Most papers were published within one month after acceptance by editors. Zootaxa has established itself as a major international journal in systematic zoology.